Simultaneous identification of reaction and inactivation kinetics of an enzyme‐catalyzed carboligation. (27th July 2018) - Ohs, Rüdiger; Leipnitz, Martin; Schöpping, Marie; Spiess, Antje C.
Abstract : Thiamine diphosphate (ThDP)‐dependent enzymes catalyze a broad range of reactions with excellent enantioselectivity. Among these reactions, carboligations of aldehydes are of particular interest since the products, chiral hydroxy ketones, are valuable building blocks in the pharmaceutical industry. However, the substrates, for example, benzaldehyde, inactivate the biocatalysts, for example the ThDP‐dependent benzaldehyde lyase from Pseudomonas fluorescens ( Pf BAL). Because only few mechanistic kinetic models for carboligation and simultaneous inactivation are available today, we quantitatively determined the reaction kinetics and inactivation of the self‐carboligation of benzaldehyde yielding the product ( R )‐benzoin catalyzed by Pf BAL directly from progress curves using model‐based experimental analysis. Discrimination of several inactivation models identified the substrate‐dependent inactivation by benzaldehyde to be significant. Sensitivity analysis and optimal experimental design improved parameter precision significantly, to between 4 and 26% relative standard deviation while maintaining the necessary number of 13 experiments moderate. The developed mechanistic kinetic model will enable to perform a model‐based process optimization to circumvent the substrate‐dependent enzyme inactivation. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 2018 © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:1081–1092, 2018